PERBANDINGAN EFEKTIVITAS BUAH STROBERI (Fragaria x ananassa) DENGAN BUAH JERUK NIPIS (Citrus aurantifolia) SEBAGAI BAHAN ALAMI PEMUTIH GIGI SECARA IN VITRO - Nia Nurhaeni; Denas Symond; Bambang Ristiono (Faculty of Dentistry Universitas Andalas, 2017)
One of the aesthetic problem which had bother and become a complaint was teeth discoloration that can be overcome by dental bleaching procedures. The use of tooth whitening ingredient can cause side effects such as tooth sensitivity and mucous irritation. Therefore, many researchers have been looking for a safer alternatives materials to be used as tooth whitening ingredients including Strawberry (Fragaria x ananassa) contain of elegat acid and malic acid and Lime (Citrus aurantifolia) contain of citric acid which have potential to whiten the teeth. The purpose of this research is to determine differences strawberry and lime fruit as a natural ingredient of tooth whitening. This research used in vitro laboratory experiment method by using 30 post-extraction premolar on teeth divided into three groups, namely the treatment of strawberry concentration of 100% (K1), the treatment group lime concentration of 2.5% (K2 ) and the treatment control group carbamide peroxide 10% (K3). Color changes measurements was observed pretest and posttest by 15 observers using Shade Guide VITAPAN classical. The research showed that strawberry concentration of 100% have an average difference in the color of teeth is 6.40, lime concentration of 2.5 at 6.20 and carbamide peroxide 10% as the control group amounted to 3.20. Based on the Kruskal Wallis test there are differences in the average value of the observation color of the teeth was significant (P <0.05) and continued with different test further the Post Hoc Test Mann Whitney gained significant difference (p> 0.05) between treatment groups strawberry 100% with carbamide peroxide 10%, lime and 2.5% carbamide peroxide 10%, while among the treatment groups strawberries 100% with 2.5% lime fruit is not significantly different because it has a value of p> 0.05. Strawberry concentration of 100% more effective to whiten teeth than lime concentration of 2.5%, but there is no significant difference in teeth whitening, while lime is more effective than carbamide peroxide 10%. Keywords:Strawberry, lime, carbamide peroxide 10%, tooth whitening.